Android-Based Learning Media Using Problem Based Learning on Physics Learning of Senior High School Students - Reni Tania; Jumadi Jumadi; Falentinus Tolino (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2020)
This study aims to determine Android-based physics learning media (ABLM) with developed Problem Based Learning (PBL) learning. This research uses R&D research. The research steps were guided by the 4D model (Define, Design, Develop, and Disseminate). The research data were obtained through the product feasibility assessment of expert validators (media experts and material experts) and questionnaire responses from class X students of SMA Negeri 1 Tempilang. Collecting research data using validation sheets and questionnaires. Data collected using descriptive analysis. The results of product feasibility by media experts with an average score of 3.72, product feasibility by material experts of 3.76, and student response results of 3.64. The results of expert validation analysis and student responses were in the "Very Good" category. The ABLM media with PBL learning was declared feasible and suitable for learning physics.